An In Vitro Comparison of Propex II Apex Locator to Standard Radiographic Method - Pishipati, Kalyan Vinayak Chakravarthy (Iranian Endodontic Journal, 2013)
Introduction: The aim of this in vitro study was to compare the accuracy of radiography in assessing working length to Propex II apex locator. Materials and Methods: Thirty single canal extracted human teeth with patent apical foramen were selected. Access cavities were prepared. Anatomic length (AL) was determined by inserting a K-file into the root canal until the file tip was just visible at the most coronal aspect of the apical foramen; subsequently 0.5 mm was deducted from this measured length. Working length by radiographic method (RL) was determined using Ingle’s method. Propex II apex locator was used to determine the electronic working length (EL). From these calculated lengths, AL was deducted to obtain D-value. D-value in the range of +/-0.5 mm was considered to be acceptable. Results: The percentage accuracy of RL and Propex II apex locator was 76.6% and 86.6%, respectively. Paired t-test revealed significant difference between the RL and Propex II apex locator (P<0.05). Conclusion: Under these in vitro conditions, Propex II apex locator has determined working length more accurately than radiographic method.